Closed life-cycle aquaculture of sea lettuce (Ulva fenestrata): performance and biochemical profile differ in early developmental stages - Steinhagen, Sophie; Larsson, Karin; Olsson, Joakim; Albers, Eva; Undeland, Ingrid; Pavia, Henrik; Toth, Gunilla B. (Frontiers in Marine Science, 2022)
Sea lettuce (Ulva) aquaculture has increased the last decade due to high productivity, wide environmental tolerance, and interesting functional and nutritional properties of the crop. Research focus has mainly been on adult biomass production, but knowledge of performance and biochemical content of early developmental stages – which are the basis to any large-scale production - is still limited. The life-history of Ulva alternates between a diploid sporophytic life-stage and a haplontic gametophytic life-stage. Whereas the sporophyte give raise to recombinant gametophytes through zoids, gametophytes can give raise to parthenogenetically developing, clonal gametes in absence of a mating partner. This study shows that recombinant gametophytes have a faster ontogenetic development, higher growth rate, as well as higher protein, fatty acid, and pigment contents compared to clonal gametophytes of the crop Ulva fenestrata. Nutrient addition is required for a normal development, but temperature and swarmer density have relatively small effects on the hatchery success, relative growth rate and biochemical profile of the juvenile biomass. Our study reveals that the selection of the life-history-phase in novel sea lettuce crop strains could largely contribute to the emerging seaweed aquaculture sector.